An Interview with Rob Walser in Toronto - Walser, Rob; Magdanz, Teresa; Wood, Simon (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2001)
In late autumn of 2000, thousands of music scholars gathered at an international mega-conference in Toronto. On that occasion, Teresa Magdanz and Simon Wood met privately with Robert Walser, Professor of Musicology at UCLA, to discuss a number of questions pertinent to popular music studies, many of which were raised at the conference. In their interview they explore the trajectory of his work, his thoughts on the relationship between music scholarship and performance, and his reflections on popular music and the academy, the implications of which extend beyond popular music studies to challenge the broader scope and practice of musicological scholarship.